Statistically significant but clinically unimportant: a systematic review and meta-analysis of the analgesic benefits of erector spinae plane block following breast cancer surgery. Issue 1 (9th November 2020) - Hussain, Nasir; Brull, Richard; Noble, Jordan; Weaver, Tristan; Essandoh, Michael; McCartney, Colin JL; Abdallah, Faraj W
Abstract : The novel erector spinae plane block (ESPB) has been reported to provide important postoperative analgesic benefits following a variety of truncal and abdominal surgical procedures. However, evidence of its analgesic efficacy following breast cancer surgery, compared with parenteral analgesia, is unclear. This meta-analysis evaluates the analgesic benefits of adding ESPB to parenteral analgesia following breast cancer surgery. Databases were searched for breast tumor resection trials comparing ESPB to parenteral analgesia. The two co-primary outcomes examined were 24-hour postoperative oral morphine equivalent consumption and area-under-curve of rest pain scores. We considered reductions equivalent to 3.3 cm.h and 30 mg oral morphine in the first 24 hours postoperatively for the two co-primary outcomes, respectively, to be clinically important. We also assessed opioid-related side effects and long-term outcomes, including health-related quality of life, persistent postsurgical pain and opioid dependence. Results were pooled using random effects modeling. Twelve trials (699 patients) were analyzed. Moderate quality evidence suggested that ESPB decreased 24-hour morphine consumption and area-under-curve of rest pain by a mean difference (95% CI) of −17.60 mg (−24.27 to −10.93) and -2.74 cm.h (−3.09 to −2.39), respectively; but these differences were not clinically important. High-quality evidence suggested that ESPB decreased opioid-related side effects compared with parenteral analgesia by an OR (95% CI) of 0.43 (0.28 to 0.66). None of the studies evaluated long-term block benefits. Adding ESPB to parenteral analgesia provides statistically significant but clinically unimportant short-term benefits following breast cancer surgery. Current evidence does not support routine use of ESPB. Given the very modest short-term benefits and risk of complications, the block should be considered on a case-by-case basis.